1989
DOI: 10.2172/6300307
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of MHTGR licensing basis accident scenarios

Abstract: LIST OF FIGURES xv LIST OF TABLES xix A draft of the report was reviewed by Drs. James G. Guppy and Gregory J. Van Tuyle at BNL and Dr. Peter Williams at the NRC. Early drafts of the report were typed by Mrs. Amalia Ruggiero. The final draft and final report were typed by Mrs. Linda Hanlon. The author gratefully acknowledges all of the help and support he received.-xx i-* Time at which heat leaving vessel exceeds decay heat, i.e., net cooldown of reactor vessel and internals begins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…For fin spacing of about 10 cm and 15 cm fin lengths, at an RCCs panel radius of about 3.4 m, the curvature effects are indeed small. The effect of axial radiation was found to be very small in the reactor cavity (Kroeger, 1989) and would be even less at the temperature levels within the RCCS channels.…”
Section: B-2 Radiation View Factors In An Annular Cylindrical Cavitymentioning
confidence: 94%
See 2 more Smart Citations
“…For fin spacing of about 10 cm and 15 cm fin lengths, at an RCCs panel radius of about 3.4 m, the curvature effects are indeed small. The effect of axial radiation was found to be very small in the reactor cavity (Kroeger, 1989) and would be even less at the temperature levels within the RCCS channels.…”
Section: B-2 Radiation View Factors In An Annular Cylindrical Cavitymentioning
confidence: 94%
“…The reaction rates were raised up by one order and down by two orders. The result for several very conservative air ingress transients during core-heatup transients showed that the effect of ali these variations on the amount of graphite oxidized was negligible, because essentially ali oxygen entering the core will react and the amount of carbon oxidized is limited by the gas flow through the core, which remains small due to its long and narrow coolant passages [Kroeger, 1989].…”
Section: -38mentioning
confidence: 99%
See 1 more Smart Citation
“…Other safety issues related to graphite oxidation include production of combustible gases (Kroeger 1989;Palmer, Sibulkin, Strehlow, & Yang 1978) and liberation of FPs. Provided circulating quantities of dust are indeed small, these issues are only important for structural graphite, not dust.…”
Section: Gap Analysismentioning
confidence: 99%